Assessment of the Relationship of Ankle-Brachial Index With Coronary Artery Disease Severity - Petracco,Andrea Mabilde (2018)
Abstract Background: Peripheral Artery Disease (PAD) is associated with cardiovascular events and can be diagnosed and estimated by use of the Ankle-Brachial Index (ABI). ABI is a worsening factor in the stratification of cardiovascular risk, but its contribution to define the severity of coronary artery disease has not been well established. Objectives: To compare the ABI value with the coronary atherosclerotic disease severity by use of the Syntax Score (SS) in patients with Acute Coronary Syndrome (ACS). Methods: This prospective study measured the ABI of all patients with ACS consecutively admitted to the São Lucas Hospital of PUCRS from May to September 2016, and compared the ABI values with the SS and ACS types of those patients. The analyzes were performed considering the 95%confidence interval (a = 5%). Results: This study assessed 101 patients [mean age, 62.6 ± 12.0 years; 58 men (57.4%)], 74 (82.2%) were hypertensive, 33 (45.8%) had diabetes and 46 (45,5%) had ST-elevation acute myocardial infarction (STEMI). The PAD severity was not related to the anatomical severity of the coronary artery disease (CAD). We found a significant association of intermediate SS with non-ST-elevation acute myocardial infarction (NSTEMI), and of low SS with unstable angina (UA) [OR (95% CI): 1.11 (1.03-1.20) (p = 0.004)], which remained after multivariate analysis adjusted to age, smoking, family history of CAD and previous CAD [(OR 95%): 1.13 (1.02-1.25) (p = 0.019)]. Conclusions: Patients with ABI < 0.9 showed no association with higher disease complexity determined by the SS in patients with ACS. Patients with NSTEMI were more associated with an intermediate risk on the SS.